Morphological Awareness Intervention: Study of a Child With a History of Speech and Language Impairment. (August 2015) - McLeod, Angela N.; Apel, Kenn
We investigated the effect of a morphological awareness intervention on the morphological awareness and reading skills of a 6-year-old student who was struggling with early reading skills and had a history of speech and language impairment. We conducted a 7-week intervention designed to increase the student's awareness of affixes and the meaning relations between base words and their inflected and derived forms. The student received twenty-five, 35-min sessions, typically receiving three to four sessions per week. Results revealed clinically relevant gains in morphological awareness abilities and word-level (sight word) reading skills. Gains were noted in pseudoword reading and reading comprehension, but they did not reach clinically relevant levels. The results of our case study suggest that our relatively short, but somewhat intensive, morphological awareness intervention led to clinically relevant gains in morphological awareness skills and word-level reading abilities for our 6-year-old student with a history of speech and language impairment. Initial clinical implications, limitations of the study, and research suggestions are discussed.